2021
DOI: 10.1002/tox.23388
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA inhibits gastric cancer cell stemness through inducing ferroptosis

Abstract: Tanshinone IIA is the active constituent extracted from Salvia Miltiorrhza. Numerous studies have shown that Tanshinone IIA could inhibit tumor proliferation and metastasis, including gastric cancer. However, the effect of Tanshinone IIA on gastric cancer cell stemness stays unclear. Here, we found that Tanshinone IIA could reduce gastric cancer cell stemness through detecting spheroid‐forming, flow cytometry analysis, and the expression of stemness markers (OCT3/4, ALDH1A1, and CD44). Mechanistically, Tanshin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 42 publications
1
45
0
Order By: Relevance
“…Su (2018) found that Tan-IIA inhibited human gastric cancer AGS cells; one of the molecular mechanisms may be through decreasing the protein expression of VEGFR and HER2, then blocking the Ras/Raf/MEK/ ERK pathway to induce the activation of PARP and caspase-3 to induce apoptosis. 'It is worth mentioning that Ni et al (2022) and Guan et al (2020) pointed out that Tanshinone IIA inhibited the stemness of gastric cancer cells partly by inducing ferroptosis. Chen et al (2017) showed that the tuber of Amorphophallus konjac could increase cell apoptosis and induce cell cycle arrest.…”
Section: Figurementioning
confidence: 99%
“…Su (2018) found that Tan-IIA inhibited human gastric cancer AGS cells; one of the molecular mechanisms may be through decreasing the protein expression of VEGFR and HER2, then blocking the Ras/Raf/MEK/ ERK pathway to induce the activation of PARP and caspase-3 to induce apoptosis. 'It is worth mentioning that Ni et al (2022) and Guan et al (2020) pointed out that Tanshinone IIA inhibited the stemness of gastric cancer cells partly by inducing ferroptosis. Chen et al (2017) showed that the tuber of Amorphophallus konjac could increase cell apoptosis and induce cell cycle arrest.…”
Section: Figurementioning
confidence: 99%
“…As a widely used TCM compound, TanIIA has already been investigated as a primary or adjuvant therapy with beneficial effects on HNSCC patient survival ( 10 ). The latest studies have confirmed that TanIIA increased the level of lipid peroxides and decreased glutathione levels in gastric cancer cells, both of which are markers of ferroptosis ( 25 ). Guan et al ( 8 ) proved that TanIIA caused decreased intracellular glutathione levels and cysteine levels and increased intracellular reactive oxygen species (ROS) levels.…”
Section: Discussionmentioning
confidence: 94%
“…For down-regulated genes by TRPs, ALDH1A1 modulates the activity of lysosomal autophagy inhibitors in cancer cells ( Piao et al, 2017 ). ALDH1A1 was also involved in ferroptosis of gastric cancer ( Ni et al, 2022 ). Aberrant promoter methylation of EFHD1 was highly positive in colorectal cancer plasma samples, and they might be useful in detection of early-stage colorectal cancer ( Takane et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%